2014
DOI: 10.1111/ajt.12669
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus Inhibits Anti-HLA I Antibody-Mediated Endothelial Cell Signaling, Migration and Proliferation More Potently Than Sirolimus

Abstract: Antibody (Ab) crosslinking of HLA I molecules on the surface of endothelial cells triggers proliferative and pro-survival intracellular signaling, which is implicated in the process of chronic allograft rejection, also known as transplant vasculopathy. The purpose of this study was to investigate the role of mammalian target of rapamycin (mTOR) in HLA I antibody-induced signaling cascades. Everolimus provides a tool to establish how the mTOR signal network regulates HLA I-mediated migration, proliferation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 73 publications
8
95
1
Order By: Relevance
“…In addition the analysis of the Scientific Registry of Transplant Recipients (SRTR) database (n = 26414) showed an increased risk of all-cause mortality in patients with hepatitis C treated with sirolimus (HR = 1.29; 95%CI: 1.08-1.55) [134] . Everolimus has a selective effect on mTOR complex 1, and it has been proposed to be more potent than sirolimus [135] , and with an improved metabolic profile [136] . Unfortunately the evidence linking everolimus and HCC recurrence after LT is lacking.…”
Section: Strategies To Improve Outcome After Liver Transplantationmentioning
confidence: 99%
“…In addition the analysis of the Scientific Registry of Transplant Recipients (SRTR) database (n = 26414) showed an increased risk of all-cause mortality in patients with hepatitis C treated with sirolimus (HR = 1.29; 95%CI: 1.08-1.55) [134] . Everolimus has a selective effect on mTOR complex 1, and it has been proposed to be more potent than sirolimus [135] , and with an improved metabolic profile [136] . Unfortunately the evidence linking everolimus and HCC recurrence after LT is lacking.…”
Section: Strategies To Improve Outcome After Liver Transplantationmentioning
confidence: 99%
“…HLA antibodies promote activation of intracellular signaling in vitro and in animal models (141)(142)(143)(144)(145)(146)(147). Several studies have demonstrated that detection of phosphorylated signaling molecules that are activated downstream of HLA cross-linking, including S6 ribosomal protein and S6 kinase, aids in detection of AMR in cardiac allografts (101,102,148).…”
Section: Microvascular Inflammation and Endothelial Injurymentioning
confidence: 99%
“…Extensive in vitro evidence points to an intrinsic role for HLA signaling within the graft vasculature that promotes angiogenic and inflammatory responses (Figure 2). For example, cross-linking of HLA class I with bivalent antibodies mimics trans interactions with T cell receptors, triggering phosphorylation of Src and focal adhesion kinases (FAKs), mTOR, ERK, and S6 ribosomal protein in endothelial and smooth muscle cells (143,145,146). These signaling pathways promote cytoskeletal rearrangements, as well as increased wound healing and cell growth (143,145,146).…”
Section: Microvascular Inflammation and Endothelial Injurymentioning
confidence: 99%
See 2 more Smart Citations